LIFE-Projekt "Salzburger Salzachauen". Auen-Renaturierung mit Mehrfachnutzen. - Riehl, Bernhard (Forum Landschaftsplanung - AbsolventInnenverband, 2020)
Since 2015, extensive floodplain restoration has been implemented in the "Salzachauen" Natura 2000 site north of the city of Salzburg with the help of EU LIFE funding. The acquisition of almost 130 hectares of wetland including hunting and fishing rights creates ideal management options for developing the alluvial forest ecosystem in the sense of Natura 2000 protected assets. In addition to restoration measures, elaborate visitor facilities were implemented. They serve to guide visitors and create acceptance for the project and the protected area.

Seit 2015 wird im Natura-2000-Gebiet "Salzachauen" mithilfe der EU-LIFE-Förderung eine großflächige Auen-Renaturierung, Salzburgs größtes Naturschutzprojekt, umgesetzt. Neben Renaturierungsmaßnahmen wurden aufwendige Besucher*inneneinrichtungen mit gestalterischem Anspruch realisiert. Die Arbeiten sind zu großen Teilen fertiggestellt. Ein günstiger Zeitpunkt für eine erste Bilanz.
Keywords: Renaturierung; Auenlandschaft; Naturschutz; Landschaftsschutz; Flusslandschaft; Nachhaltige Entwicklung; Projekt